Pengaruh Penggunaan Chat Generative Pre-Trained Transformer (Chat GPT) terhadap Kualitas Pembelajaran Mahasiswa Pendidikan Agama Islam di Universitas Islam Negeri Palopo - Sulfikar, Sulfikar; Hamdany, M. Zuljalal Al; Nursyamsi, Nursyamsi (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of Chat GPT use on the quality of Islamic education learning among students at UIN Palopo. This study uses a descriptive quantitative research design. The population in this study consists of 127 Islamic education students from the 2023 cohort, with a sample size of 56 students selected using the Yamane formula. The data collection techniques used were questionnaires and documentation studies. Data analysis was performed using descriptive statistical analysis and inferential statistical analysis tests in the form of normality and linearity tests, simple linear regression tests, and hypothesis testing using the t-test. The results showed that there was a positive effect between the use of Chat GPT and the quality of learning among Islamic Education students at UIN Palopo. This was proven by a significance value smaller than the probability (0.000 < 0.05) and a Tcount value exceeding Ttable (6.290 > 1.67356), so that H0 was rejected and H1 was accepted. Thus, the use of Chat GPT was proven to have a significant effect on learning quality. The magnitude of this influence is indicated by an R-square value of 42.3%.